Are measures and related symptoms of cachexia recorded as outcomes in gastrointestinal cancer chemotherapy clinical trials? - Ross Valaire; Frances Garden; Valentina Razmovski‐Naumovski (Wiley, 2024)
Abstract Background Cachexia is prevalent in gastrointestinal cancers and worsens patient outcomes and chemotherapy compliance. We examined to what extent registered gastrointestinal cancer chemotherapy clinical trials record measures and related symptoms of cachexia as outcomes, and whether these were associated with trial characteristics. Methods Four public trial registries (2012-2022) were accessed for Phase II and/or III randomized controlled pancreatic, gastric, and colorectal cancer chemotherapy trial protocols. Trial outcome measures of overall survival and toxicity/side effects, and those related to cachexia [physical activity, weight/body mass index (BMI), dietary limitations, caloric intake, lean muscle mass] and symptoms (appetite loss, diarrhoea, pain, fatigue/insomnia, constipation, nausea, vomiting, and oral mucositis) were extracted, along with the number and types of performance status and patient‐reported outcomes (PROs) tools. Data were summarized descriptively. Chi‐square tests examined associations between outcomes and trial characteristics (cancer type, trial location, funding source, PROs tools, and commencement year). Statistical significance was set at P < 0.05. Results We included 540 trial protocols (pancreatic (35.2%), colorectal (33.3%) and gastric (31.5%)), with most trials from Europe (44.1%). Trial lead investigator was from academia (28.3%), industry (27.6%) and government (26.3%). Allied health professional involvement (26.9%) occurred at eligibility. Adjuvant therapy in trials was mainly treatment‐related (68.1%). Additional medication included anti‐nausea (2.2%) and analgesia (0.9%). Trial protocols mostly recorded overall survival (90.4%) and toxicity (78.9%), and the symptoms appetite loss (26.1%) and diarrhoea (19.1%), with the other symptoms recorded in <10% of the trials. Reporting of physical activity (P = 0.001), dietary limitations (P = 0.002), lean muscle mass (P = 0.027), appetite loss (P < 0.001), pain (P = 0.001), nausea (P = 0.012), and oral mucositis (P = 0.049) varied depending cancer type. Toxicity/side effects (P = 0.022), physical activity (P < 0.001), appetite loss, nausea, and vomiting (all P < 0.001), diarrhoea (P = 0.010), pain (P = 0.001), fatigue/insomnia (P = 0.001) varied depending on the trial location. Trial funding was predominantly from private/industry (34.3%) and influenced the reporting of overall survival (P = 0.049), weight/BMI (P = 0.005), caloric intake (P = 0.015), and pain (P = 0.031). Performance status and PROs tools were mentioned in 91.2% and 46.3% of the trials, respectively. Trials that incorporated PROs tools were more likely to report cachexia related outcomes, except for overall survival, lean muscle mass, and oral mucositis. The proportion of trials measuring weight/BMI increased with trial commencement year (P = 0.04). Conclusions Cachexia‐related outcomes were under‐recorded in gastrointestinal cancer chemotherapy trials. As trial patients experience a high symptom burden, cachexia‐relevant measures and symptoms should be assessed throughout the trial, and integrated with primary endpoints to support their progress.